Penny Postcard of Main Street in Ventura, CA - United States Post Office::::::
This penny postcard image can be dated prior to 1908, as at the end of that year Main Street had been paved and the famed streetcar tracks covered forever. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.